von Willebrand factor and cancer: A renewed interest - Franchini, Massimo; Frattini, Francesco; Crestani, Silvia; Bonfanti, Carlo; Lippi, Giuseppe (Thrombosis research, 2013)
Von Willebrand factor (VWF), the largest human plasma protein, is an adhesive multimeric glycoprotein that mediates platelet adhesion to both the subendothelial matrix and endothelial surfaces and acts as a carrier for coagulation factor VIII in the circulation. Besides its essential role in hemostasis, there is growing evidence from the literature that VWF has an additional antitumor effect, mainly by exerting negative modulation on angiogenesis and apoptosis. Current knowledge on the link between VWF and cancer is summarized in this review, based on an analysis of the most important experimental and clinical studies.